Indications of Hate Speech in the Speech Acts of Panji Gumilang on the Kick Andy Talk Show on Metro TV: A Forensic Linguistic Study - Mardhatillah, Siti Masyitha; Agustina, Agustina (Universitas Pendidikan Mandalika, 2025)
Recently, the Indonesian public has been stirred by various comments regarding several videos showing religious activities at Al-Zaytun Islamic Boarding School, which were considered deviating from religious teachings. These public comments sparked a response from the school's leader (PG), which was found to contain hate speech that was even more shocking. Therefore, this study aims to